Kajian Sumberdaya Kima dan Ekosistem Terumbu Karang untuk Pengelolaan Ekowisata Bahari di Perairan Morella, Maluku Tengah: Study of Giant Clams Resources and Coral Reef Ecosytem for Marine Ecoturism Management - Rabiyanti, Intan; Yulianda, Fredinan; Imran, Zulhamsyah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
ABSTRACT Giant clams that protected by CITES Appendix II is important marine organism as a stock in and also has potential as a marine tourism. This study aims to analyze the potential of clams which are part of the coral reef ecosystem as an alternative ecotourism management of diving and snorkeling in Morella and analyzing appropriate management strategies for the development of tourism areas in Morella. The method used for the analysis of clams is 1) the density of clams Di = ni / A; 2) diversity index H '= - (∑ni (ln (ni / N)); 3) dominance index D = ∑ [Ni / N] 2, and Analysis Hierarchy Process (AHP) method. There are five types of clams such as Tridacna maxima, T. squamosa, T. gigas, T. crocea and Hippopus hippopus. The widest distribuiton was T. maxima, which was found at each research areas and the lowest was H. Hippopus. The population of clams was found at Lettang Beach with the most species being T. squamosa. The highest percentage of coral reef cover was found at Lubang Buaya Beach at 81.10% and the lowest at station I at 55.53%. The highest number of species of reef fish is found at Lettang Beach, which is 197 types. The management strategy that needs to be prioritized is integrated management, which takes into account all aspects of ecological, economic, social and institutional aspects.